PSYCHOPATHOLOGY IN ADULTS WITH INTELLECTUAL DISABILITIES WITH OR WITHOUT EPILEPSY: A CASE CONTROL STUDY. Issue 9 (6th August 2013) - Okafor, GE; Deb, S; Cavanna, AE; Unwin, G
Abstract : Aims: Epilepsy-related factors may increase the risk of developing psychopathology in adults with intellectual disabilities (ID). We examined the patterns of problem behaviours and psychiatric disorders among adults with ID and epilepsy. Methods: We recruited 23 adults with ID and epilepsy (11 males) and a control group of 23 adults with ID alone (13 males) matched for age and ID level. The mean age of the overall sample was 41 years (SD=17). Their carers were interviewed using the Modified Overt Aggression Scale (MOAS) (which provided a total score for aggression but also separate scores for verbal aggression, and physical aggression against people, objects and self respectively), and mini PAS-ADD Interview to assess co-morbid psychiatric disorders. Results: A significantly higher proportion of adults with ID and epilepsy, compared with adults with ID alone manifested aggression against people and objects. Although there was no significant difference between the two groups in the proportion of adults meeting mini PAS-ADD Interview threshold scores for the presence of at least one psychiatric disorder, a higher proportion of patients in the non-epilepsy group (26%) compared with the epilepsy group had depression (4%). The results also showed that higher seizure frequency was associated with aggression against people and total MOAS aggression scores. Conclusions: This study supports previous research (Deb and Hunter 1991a, b) that the overall rates of psychopathology and patterns of aggressive behaviours or psychiatric disorders are similar among adults with ID with or without epilepsy, although frequent seizures increases the risk for aggression against people.